2021
DOI: 10.1039/d1sc02049h
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic C–H isocyanation/amine coupling sequence enabling high-throughput synthesis of pharmaceutically relevant ureas

Abstract: C(sp3)–H functionalization methods provide an ideal synthetic platform for medicinal chemistry; however, such methods are often constrained by practical limitations. The present study outlines a C(sp3)–H isocyanation protocol that enables...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…However, radical-chain chlorination methods that involve chlorine radical (Cl · ) as the hydrogen-atom transfer (HAT) reagent, often exhibit poor C–H site selectivity. Consequently, benzylic chlorides are commonly prepared by the reaction of benzylic alcohols with SOCl 2 or via other functional-group interconversion methods. ,,,, C–H chlorination methods that employ species other than Cl · for the HAT step can show improved selectivity. In this context, Cu catalysts, in combination with N -fluorobenzenesulfonimide as the oxidant (Cu/NFSI), promote diverse C–H functionalization and oxidative cross-coupling reactions (e.g., Figure B) that exhibit high benzylic site selectivity. These methods involve a radical-relay mechanism, in which HAT generates a diffusible benzylic radical that undergoes subsequent functionalization by Cu II and a nucleophilic coupling partner.…”
mentioning
confidence: 99%
“…However, radical-chain chlorination methods that involve chlorine radical (Cl · ) as the hydrogen-atom transfer (HAT) reagent, often exhibit poor C–H site selectivity. Consequently, benzylic chlorides are commonly prepared by the reaction of benzylic alcohols with SOCl 2 or via other functional-group interconversion methods. ,,,, C–H chlorination methods that employ species other than Cl · for the HAT step can show improved selectivity. In this context, Cu catalysts, in combination with N -fluorobenzenesulfonimide as the oxidant (Cu/NFSI), promote diverse C–H functionalization and oxidative cross-coupling reactions (e.g., Figure B) that exhibit high benzylic site selectivity. These methods involve a radical-relay mechanism, in which HAT generates a diffusible benzylic radical that undergoes subsequent functionalization by Cu II and a nucleophilic coupling partner.…”
mentioning
confidence: 99%
“…Investigation of oxidative cross-coupling of benzylic C−H substrates and N−H azoles started with ethylbenzene (1a) and ethyl 3-(trifluoromethyl)-1H-pyrazole-4-carboxylate (2a), a pyrazole featured in previous drug discovery efforts. 17 reactions, including pseudohalides (cyanide, 18 azide, 8d isocyanate 19 ), alcohols, 20 carbamates, 21 and carbon-based nucleophiles ((bpy)Zn(CF 3 ) 2 , 22 ArB(OH) 2 , 23 alkynes 24 ). 19,20,27 The above mechanistic considerations guided a survey of reaction conditions.…”
mentioning
confidence: 99%
“…17 reactions, including pseudohalides (cyanide, 18 azide, 8d isocyanate 19 ), alcohols, 20 carbamates, 21 and carbon-based nucleophiles ((bpy)Zn(CF 3 ) 2 , 22 ArB(OH) 2 , 23 alkynes 24 ). 19,20,27 The above mechanistic considerations guided a survey of reaction conditions. Initial screening data showed that Cu/ NFSI-catalyzed oxidative coupling of 1a and 2a favors the N 2 isomeric product 3aa when the reaction is conducted in chlorinated solvents PhCl and dichloromethane (DCM) (Figure 2A, entries 1 and 2; see Supporting Information for full screening details).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in high-throughput experimentation (HTE) enabled the fast examination of multiple reactions with minimum resources in a relatively short period of time. Thus, the HTE approach has been successfully applied to pharmaceutical synthesis and catalyst design. Benefitting from the HTE logic and known accessibility to both Cp X - and LX-type compounds, we envisaged generating a wide array of Cp X M­(LX) complexes in situ by simple premixing of [Cp X MCl 2 ] 2 and LX co-ligands. Moreover, we also envisioned additionally screening the metal centers and nitrenoid precursors (Scheme b, right).…”
Section: Introductionmentioning
confidence: 99%